Dendritic cells from human mesenteric lymph nodes in inflammatory and non‐inflammatory bowel diseases: subsets and function of plasmacytoid dendritic cells. Issue 1 (8th April 2013) - Hostmann, Arwed; Kapp, Kerstin; Beutner, Marianne; Ritz, Jörg‐Peter; Loddenkemper, Christoph; Ignatius, Ralf; Duchmann, Rainer; Daum, Severin; Gröne, Jörn; Hotz, Hubert; Buhr, Heinz‐Johannes; Zeitz, Martin; et al.
Summary: Plasmacytoid dendritic cells (pDC) in mesenteric lymph nodes (MLN) may be important regulators of both inflammatory and non‐inflammatory mucosal immune responses but human studies are rare. Here we compare pDC from human MLN and peripheral blood (PB) by phenotype and function. MLN from patients with or without inflammatory bowel disease (IBD) undergoing colon surgery and PB from patients with IBD and from controls were used to isolate mononuclear cells. The pDC were analysed by flow cytometry for the expression of CD40, CD80, CD83, CD86, CCR6, CCR7, CX3CR1, CD103 and HLA‐DR. Purified pDC from MLN and PB were stimulated with staphylococcus enterotoxin B (SEB), CpG‐A, interleukin‐3 (IL‐3), SEB + IL‐3, CpG‐A + IL‐3 or left unstimulated, and cultured alone or with purified allogeneic CD4 +  CD45RA +  HLA‐DR‐ T cells. Subsequently, concentrations of IL‐1β, IL‐2, IL‐4, IL‐6, IL‐8, IL‐10, IL‐12, IL‐17, interferon‐α (IFN‐α), IFN‐γ and tumour necrosis factor‐α (TNF‐α) in culture supernatants were determined by multiplex bead array. The PB pDC from IBD patients exhibited an activated and matured phenotype whereas MLN pDC and control PB pDC were less activated. CpG‐A and CpG‐A + IL‐3‐stimulated MLN pDC secreted less IL‐6 and TNF‐α compared with PB pDC from controls. Compared with co‐cultures of naive CD4 T cells with PB pDC, co‐cultures with MLN pDC contained more IL‐2, IL‐10 and IFN‐γ when stimulated with SEB and SEB + IL‐3, and less IFN‐α when stimulated with CpG‐A. MLN pDC differ phenotypically from PB pDC and their pattern of cytokine secretion and may contribute to specific outcomes of mucosal immune reactions.